Respon Bibit Salak Terhadap Pemberian Pupuk Daun - Daulay, Lalan Darham; Fahrurrozi, Fahrurrozi; Mukhtasar, Mukhtasar (Akta Agrosia, 2014)
The availability of high rate of transplanting succes is very important for early growth of snakefruit. An experiment aimed to identify both optimal concentration and frequency of foliar fertilizer application on growthof snakefruit during nursery. The experiment was conducted in Pondok Kelapa, Bengkulu Tengah, from August to October 2008. Concentration and frequency treatments were arranged in a Split Plot base on a Randomized Complete Block Design. Spraying frequency (weekly, two-weekly or three-weekly) were used as the main plot;whereas, concentration of liquid nutrient Hyponex Merah with composition of 25:5:20-N:P:K, consisted of 0, 2, 4 and 6 g L-1 water, was the sub-plot Results demonstrated that concentration of liquid nutrient significantlyaffected seedling growth with optimum concentration for plant height was 4.6 g L-1, the greatest leaf number was 39 g L-1, the largest leaf area was 4.1 g L-1, the greatest stomata number was 4.2 g L-1, the greatest chlorophyl content was 3.9 g L-1 and seedling dry weight was 4.6 g L-1. Both frequency and its combination with concentration of foliar fertilizer had no significant effects on the growth snake fruit seedlings